Ecotoxicological Assessment and Environmental Risk of the Insecticide Chlorpyrifos for Aquatic Neotropical Indicators - Marques, Márjori Brenda Leite [UNESP]; Brunetti, Isabella Alves; Faleiros, Camila Aparecida; da Cruz, Claudinei; Iqbal, Hafiz M. N.; Bilal, Muhammad; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Springer Nature, 2021)
Chlorpyrifos (CPF) is an organophosphorus insecticide detected in aquatic environments considered harmful to living beings. The aim of this research was to evaluate the ecotoxicity of CPF for neotropical aquatic organisms of distinct trophic levels (Lemna minor, Azolla caroliniana, and Wolffia brasiliensis macrophytes; Pomacea canaliculata snail; Macrobrachium acanthurus shrimp; Xiphophorus maculatus and Hyphessobrycon eques fish), to verify the risk of environmental poisoning for each organism, and to determine the best bioindicator species of aquatic contamination by the insecticide. Ecotoxicological assays were carried out with different concentrations of CPF under controlled laboratory conditions standardized for each species. IC50;7d, LC50;7d, EC50;48h, and LC50;48h values were calculated using the Trimmed Spearman Karber software with 95% confidence limits. The toxicity data were used to classify the CPF according to the ecotoxicity categories for aquatic organisms. The risk of CPF environmental poisoning was determined by the quotient method considering different environmental scenarios. The sensitivity order of neotropical aquatic organisms to chlorpyrifos was Macrobrachium acanthurus (0.002 mg L−1) > Xiphophorus maculatus (0.07 mg L−1) > Hyphessobrycon eques (1.65 mg L−1) > Pomacea canaliculata (30.66 mg L−1) > Azolla caroliniana (849.72 mg L−1) > Wolffia brasiliensis (1271.63 mg L−1) = Lemna minor (1299.60 mg L−1). The risk of poisoning by chlorpyriphos may vary according to the environmental concentration of the insecticide and the exposed trophic level. The best bioindicator and with the greatest risk of environmental poisoning was shrimp. The difference in CPF ecotoxicity for distinct aquatic trophic levels shows the relevance of evaluating the effects of contaminants considering food chains and highlights the importance of studying these levels in environmental monitoring programs. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Ecotoxicology; Fish; Macrophyte; Organophosphorus; Pesticide